SISTEM PERANCANGAN VOIP (VOICE OVER INTERNET PROTOCOL) BERBASIS COMMAND LINE INTERFACE PADA JARINGAN LOKAL - Muhammad Amin (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
Communication technology is currently growing rapidly, especially in the field of telecommunications. The rapid development of the internet and the development of multimedia applications require certain Quality of Services (QoS) requirements. However, ordinary IP networks are not designed to pass real-time multimedia services. Basically everyone who is connected to their network can exchange information and data between one person with another, be it images, sound, video, text and others, but if we use traditional telephone calls, in addition to expensive tariffs, geographical location is also important. determine the size of the costs to be incurred. Voice Over Internet Protocol (VoIP) is an innovative technology that makes the internet network or local computer network, as a medium for transmitting voice data packets so that users can communicate with each other. The test results on the Alpha Delay (Waiting Time) VOIP phone test is shorter than the WhatsApp phone, which is 17 seconds. So VoIP calls are 14 seconds superior to Whatsapp calls, taken from the difference between WhatsApp and VoIP delays, which is 17 Seconds - 3 Seconds = 14 Seconds. In Beta testing, all clients have been connected to the server and other clients. Multi Protocol Label Switching (MPLS) is a relatively new technology in the world of telecommunications networks. MPLS technology allows packets to be in the system in a shorter time than IP networks, because in MPLS networks each packet is labeled which is then used as information for the switching process to replace the IP header in the routing process. The results obtained from this study are VoIP analysis of network signal strength on VoIP and the security of using telecommunications using wireless networks.